Association Between Gestational Diabetes Mellitus and the Risks of Type-Specific Cardiovascular Diseases - Yuanyuan Mao; Yuanyuan Mao; Wenbin Hu; Bin Xia; Bin Xia; Li Liu; Xia Han; Qin Liu (Frontiers in Public Health, 2022)
ObjectiveGestational diabetes mellitus (GDM) has been linked to subsequent overall cardiovascular diseases. However, evidence on the associations of GDM with type-specific cardiovascular diseases is lacking, and findings on the potential impact of type 2 diabetes on the associations are not consistent. This study aimed to explore the associations between GDM and the risks of type-specific cardiovascular diseases.MethodsData were from 12,025 women (≥20 years) who had delivered at least one live birth in the National Health and Nutrition Examination Survey, 2007–2018. GDM history and type-specific cardiovascular diseases including coronary heart disease (CHD), heart failure and stroke were defined by self-report. We also combined our results with those from previously related publications on the associations between GDM and risks of type-specific cardiovascular diseases with a random-effect model.ResultsCompared with women without GDM, the multivariable-adjusted odds ratios (95% confidence intervals) were 1.82 (1.21–2.72) for CHD, 1.43 (0.80–2.53) for heart failure, and 1.19 (0.76–1.86) for stroke among women with a history of GDM. Type 2 diabetes was associated with 43.90, 67.44, and 63.16% of the excess odds of CHD, heart failure and stroke associated with GDM, respectively. Combining results from this study with those from previously related studies yielded odds ratios (95% confidence intervals) of 1.81 (1.60–2.05) for CHD (12 studies, 7,615,322 participants, I2= 72.6%), 1.66 (1.25–2.21) for heart failure (5 studies, 4,491,665 participants, I2= 88.6%), and 1.25 (1.07–1.46) for cerebrovascular disease (9 studies, 6,090,848 participants, I2= 77.8%).ConclusionsGDM showed stronger associations with coronary heart diseases and heart failure than cerebrovascular disease, and the excess risks are attributable, in part, to type 2 diabetes.